Unprecedented stability in Au@Co core-shell bimetallic catalyst supported on SBA-15 (Au@Co/SBA-15) for atmospheric pressure CO hydrogenation - Jain, P.; Chimote, M.; Vinod, C. P. (Materials Today Sustainability, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Bimetallic nanoparticles demonstrating <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/synergistic-effect" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about synergistic effect from ScienceDirect's AI-generated Topic Pages">synergistic effect (electronic or geometric modification) often show distinct chemical and physical properties compared with the parent metals. In catalysis, this provides opportunities to engineer solid materials with appreciable activity, selectivity, and stability. In the present study, we have synthesized Au@Co core–shell bimetallic nanoparticles by colloidal synthesis approach with a focus to study and explore the synergistic effect between Au and Co in Au@Co <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/bimetallic-catalyst" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px;" title="Learn more about bimetallic catalyst from ScienceDirect's AI-generated Topic Pages">bimetallic catalyst supported on SBA-15 on <a class="topic-link" href="https://www.sciencedirect.com/topics/engineering/fischer-tropsch" style="background-color: transparent; text-decoration-line: underline; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); word-break: break-word; text-underline-offset: 1px; font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;" title="Learn more about Fischer Tropsch from ScienceDirect's AI-generated Topic Pages">Fischer Tropsch<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> (FT) reaction. The deactivation of catalyst is a significant drawback in CO hydrogenation (syngas conversion/FT synthesis), and the present study provides the design of a new material, which resists the surface cobalt oxide formation and inactive coke formation and gives efficient CO conversion with high stability.

Unveiling the roles of lattice strain and descriptor species on pt-like oxygen reduction activity in Pd-Bi catalysts - Sarkar, Shreya; Ramarao, S. D.; Das, Tisita; Das, Risov; Vinod, C. P.; Chakraborty, Sudip; Peter, Sebastian C. (ACS Catalysis, 2021)
A facile non-template-assisted mechanical ball milling technique was employed to generate a PdBi alloy catalyst. The induced lattice strain upon the milling time caused a shift of the d-band center, thereby enhancing the oxygen reduction reaction (ORR) catalytic activity. Additionally, the Pd-O reduction potential and adsorbed OH coverage used as descriptors stipulated the cause of the enhanced ORR activity upon the increased milling interval. Redox properties of surface Pd are directly correlated with a positive shift in the Pd-O reduction potential and OH surface coverage. Hence, by deconvoluting the lattice strain and the role of the descriptor species we achieved a catalyst system with a specific activity 5.4X higher than that of commercial Pt/C, as well as an improved durability. The experimental observation is well-corroborated by a theoretical simulation done by inducing strain to the system externally.
Keywords: charge-transfer; electrocatalysis; fuel cell; Lattice strain; oxygen reduction; Pt-like activity

Ultrathin twisty PdNi alloy nanowires as highly active ORR electrocatalysts exhibiting morphology-induced durability over 200 K cycles - Sahoo, Lipipuspa; Garg, Reeya; Kaur, Komalpreet; Vinod, C. P.; Gautam, Ujjal K. (Nano Letters, 2022)
Even though the anion exchange membrane fuel cells have many advantages, the stability of their electrocatalysts for oxygen reduction reaction (ORR) has remained remarkably poor. We report here on the ultrathin twisty PdNi-alloy nanowires (NWs) exhibiting a very low reaction overpotential with an E1/2 ∼ 0.95 V versus RHE in alkaline media maintained over 200 K cycles, the highest ever recorded for an electrocatalyst. The mass activity of the used NWs is >10 times higher than fresh commercial Pt/C. Therein, Ni improves the Pd d-band center for a more efficient ORR, and its leaching continuously regenerates the surface active sites. The twisty nanowire morphology imparts multiple anchor points on the electrode surface to arrest their detachment or coalescence and extra stability from self-entanglement. The significance of the NW morphology was further confirmed from the high-temperature durability studies. The study demonstrates that tailoring the number of contact points to the electrode-surface may help realize commercial-grade stability in the highly active electrocatalysts.

Unravelling faradaic electrochemical efficiencies over Fe/Co spinel metal oxides using surface spectroscopy and microscopy techniques - Kashyap, Varchaswal; Pandikassala, Ajmal; Singla, Gourav; Khan, Tuhin Suvra; Haider, M. Ali; Vinod, C. P.; Kurungot, Sreekumar (Nanoscale, 2022)
Cobalt and iron metal-based oxide catalysts play a significant role in energy devices. To unravel some interesting parameters, we have synthesized metal oxides of cobalt and iron (i.e. Fe2O3, Co3O4, Co2FeO4 and CoFe2O4), and measured the effect of the valence band structure, morphology, size and defects in the nanoparticles towards the electrocatalytic hydrogen evolution reaction (HER), the oxygen evolution reaction (OER) and the oxygen reduction reaction (ORR). The compositional variations in the cobalt and iron precursors significantly alter the particle size from 60 to <10 nm and simultaneously the shape of the particles (cubic and spherical). The Tauc plot obtained from the solution phase ultraviolet (UV) spectra of the nanoparticles showed band gaps of 2.2, 2.3, 2.5 and 2.8 eV for Fe2O3, Co3O4, Co2FeO4 and CoFe2O4, respectively. Further, the valence band structure and work function analysis using ultraviolet photoelectron spectroscopy (UPS) and core level X-ray photoelectron spectroscopy (XPS) analyses provided better structural insight into metal oxide catalysts. In the Co3O4 system, the valence band structure favors the HER and Fe2O3 favors the OER. The composites Co2FeO4 and CoFe2O4 show a significant change in their core level (O 1s, Co 2p and Fe 2p spectra) and valence band structure. Co3O4 shows an overpotential of 370 mV against 416 mV for Fe2O3 at a current density of 2 mA cm(-2) for the HER. Similarly, Fe2O3 shows an overpotential of 410 mV against the 435 mV for Co3O4 at a current density of 10 mA cm(-2) for the OER. However, for the ORR, Co3O4 shows 70 mV improvement in the half-wave potential against Fe2O3. The composites (Co2FeO4 and CoFe2O4) display better performance compared to their respective parent oxide systems (i.e., Co3O4 and Fe2O3, respectively) in terms of the ORR half-wave potential, which can be attributed to the presence of the oxygen vacancies over the surface in these systems. This was further corroborated in density functional theory (DFT) simulations, wherein the oxygen vacancy formation on the surface of CoFe2O4(001) was calculated to be significantly lower (similar to 50 kJ mol(-1)) compared to Co3O4 (001). The band diagram of the nanoparticles constructed from the various spectroscopic measurements with work function and band gap provides in-depth understanding of the electrocatalytic process.

Unravelling the Cu-Co nanoparticle synergy over Ceria-Zirconia support toward efficient reverse water gas shift (RWGS) conversion under H2 lean conditions - Jagtap, Anuradha Vijay; Bamnia, Mahesh Kumar; Maibam, Ashakiran; Bajpai, Jyotsna Paliwal; Gupta, Sharad; Thomas, Sharon K.; Dabke, Niteen B.; Vinod, C. P. (Chemical Engineering Journal, 2025)
CO2 emissions leading to global warming and environmental and socio-economic issues have propelled the research community to develop technologies capable of capturing and converting CO2 into valuable products. Controlling the selectivity toward platform molecules like CO, methanol, or methane is a fundamental challenge in CO2 hydrogenation. Supported cobalt nanoparticles are known for hydrocarbon production through FischerTropsch (FT) reaction, and Cu-based catalysts are known for reverse water gas shift (RWGS) reaction. Here, we show that d-band centre can be carefully modulated by making bimetallic combinations of Cu and Co for a highly active RWGS catalyst. An oxygen vacancy-rich nanostructured ceria-zirconia (CZ) support with Cu nanoparticles (2 wt%) modified with as low as 0.05 wt% Co shows excellent conversion for CO2 hydrogenation and selectivity for CO below 500 degrees C. The optimized catalyst shows CO2 conversion even under hydrogen lean conditions (H2/ CO2 ratio 0.5:1), with a breakthrough rate of 206023 mmol/gmetal/h for CO at 600 degrees C, having H2 utilization of 80% for the RWGS process.
Keywords: Bimetallic catalyst; Ceria-zirconia; CO 2 hydrogenation; Cobalt catalyst; Copper catalyst; Reverse water gas shift (RWGS); synergistic effect